Uncovering hidden genetic variations: long-read sequencing reveals new insights into tuberous sclerosis complex - Duan, Jing; Pan, Shirang; Ye, Yuanzhen; Hu, Zhanqi; Chen, Li; Liang, Dachao; Fu, Tao; Zhan, Lintao; Li, Zhuo; Liao, Jianxiang; Zhao, Xia (Frontiers in Cell and Developmental Biology, 2024)
Tuberous sclerosis is a multi-system disorder caused by mutations in either TSC1 or TSC2. The majority of affected patients (85%-90%) have heterozygous variants, and a smaller number (around 5%) have mosaic variants. Despite using various techniques, some patients still have "no mutation identified" (NMI).We hypothesized that the causal variants of patients with NMI may be structural variants or deep intronic variants. To investigate this, we sequenced the DNA of 26 tuberous sclerosis patients with NMI using targeted long-read sequencing.We identified likely pathogenic/pathogenic variants in 13 of the cases, of which 6 were large deletions, 4 were InDels, 2 were deep intronic variants, 1 had retrotransposon insertion in either TSC1 or TSC2, and 1 was complex rearrangement. Furthermore, there was a de novo Alu element insertion with a high suspicion of pathogenicity that was classified as a variant of unknown significance.Our findings expand the current knowledge of known pathogenic variants related to tuberous sclerosis, particularly uncovering mosaic complex structural variations and retrotransposon insertions that have not been previously reported in tuberous sclerosis. Our findings suggest a higher prevalence of mosaicism among tuberous sclerosis patients than previously recognized. Our results indicate that long-read sequencing is a valuable approach for tuberous sclerosis cases with no mutation identified (NMI).